Teologia „małej ojczyzny” ks. Franciszka Mantheya - Babiński, Jarosław (Warszawskie Studia Teologiczne, 2019)
Father Franciszek Manthey (1904–1971) is a man shaped by two cultures: Polish and German. This is typical of the Pomerania inhabitants in his generation. This is a great cultural inheritance, but often becomes problematic when it comes to determining national belonging. Such a particular situation raised in him the question of national identification which resulted in a theological reflection on the “little homeland” (German: Heimat). This became the starting point to create an interesting concept of national-religious identity, which he builds in relation to biblical theology, creatology and theological anthropology. Manthey claims that a person by virtue of its ontological structure, corporeal and spiritual, has a twofold sense of home. First, this is a little homeland – a country of childhood, growth and development, determining personal worldview and values. The other is God – the ultimate goal and homeland of man. Such a concept of man determines the attitudes of each individual which manifests itself in the space of faith by fulfilling duties to the small homeland and to the service of God.